Nationhood in world politics - Wan Hashim Haji Wan Teh Profesor Emeritus Dato' Dr. 1949-; Wan Norhasniah Wan Husin (Universiti Pertahanan Nasional Malaysia, 2015)
This is a compilation of essays and lecture notes to meet the need of students at UPNM who are registered for the subject of Nationhood in World Politics which is a University subject newly introduced since the first semester of academic session 2014/15. The purpose of this subject is to develop in them an inquisitive mind and to instil the values of love for knowledge, particularly on politics and current world affairs.